Long-Term Efficacy of Selective Laser Trabeculoplasty in Pseudophakic Patients – A “Real-Life” Analysis - Lindegger, D. J.; Jaggi, G. P.; Bauer, G.; Zweifel, S.; Töteberg-Harms, M.; Hirn, C.; Zehnder, S.; Funk, J. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: The aim of this study was to report on the course and long-term effect of selective laser trabeculoplasty on intraocular pressure of pseudophakic patients suffering from open angle glaucoma or ocular hypertension with insufficient intraocular pressure lowering despite maximally tolerated topical and systemic intraocular pressure lowering medication. Patients and Methods: A retrospective chart review of patients who underwent selective laser trabeculoplasty (360°) between 2008 and 2010 at the University hospital Zurich was undertaken. Intraocular pressure values before intervention, on the day of the intervention, 1 day, 1 month, 3 months and every 3 months up to 43 months after the intervention were analysed with respect to lens status. Results: Out of 153 treated eyes of 111 patients (mean age 70.6 years ± 11.13 SD) 40 were pseudophakic. Mean baseline intraocular pressures were 19.00 mmHg ± 4.61 in the pseudophakic group and 20.12 mmHg ± 4.89 in the phakic group. One month after selective laser trabeculoplasty intraocular pressure reduction measured between − 0.33 and − 4.10 mmHg (CI 95 %) in the pseudophakic group and between − 3.64 and − 5.58 mmHg (CI 95 %) in the phakic group, the difference at this time point was significant (p = 0.01). Beyond one month after selective laser trabeculoplasty there was no statistically significant difference in intraocular pressure reduction between pseudophakic and phakic patients. The mean decrease in intraocular pressure from baseline to the last follow-up of 43 months was 0.67 mmHg in the pseudophakic group and 0.25 mmHg in the phakic group (p = 0.72). Conclusions: One month after selective laser trabeculoplasty pseudophakic patients showed a statistically significant diminished reduction of intraocular pressure compared to phakic patients. Later on there was no statistically significant difference in intraocular pressure reduction between pseudophakic and phakic patients. Therefore we conclude that there was no clinically relevant influence of pseudophakia on the long-term effect of selective laser trabeculoplasty.
Keywords: selective laser trabeculoplasty; open angle glaucoma; pseudophakia; intraocular pressure